Separation of Corrosion-affecting Parameters of Formed Products – A New Strategy Using X-ray Diffraction and Corrosion Tests Under in-situ Tensile Load. (2015) - Mehner, T.; Bauer, A.; Nickel, D.; Binotsch, C.; Awiszus, B.; Lampke, T.
Abstract: The effects of several parameters on corrosion behavior cannot be separated by currently available methods. A new approach is described that combines X-ray diffraction, corrosion and tensile tests, which allows for the separation of the corrosion-affecting influences like residual stresses. It is demonstrated that the studied DC04 sheets become less noble with increasing tensile stress. Using the results, finite element method simulations can be applied to predict the corrosion behavior of the material and enhance its production and processing routes with respect to corrosion.